A comprehensive approach to the study of the housing sector in Iraq with special reference to needs, standards, inputs, density and costs as factors in the analysis of housing problems in Baghdad - al-Adhami., M.B. (1975)
Iraq has a stock of buildings, particularly dwellings, many of which are neither physically fit nor capable of meeting the economic and social needs of today. Many people, particularly in the cities, live in overcrowded and insanitary conditions. Many dwellings are badly located and mixed with derelict land. Population is expected to grow and even without any rise in standards, this would greatly increase the need for building and works of all kinds.